The Reality of Traditional Industry and Crafts in Algeria and the Mechanisms of its Development - عقون , Charaf (Milev Journal of Research and Studies, 2019)
This study aims at clarifying the reality of the traditional industry and crafts in Algeria and highlighting the mechanisms of upgrading traditional industry and crafts in Algeria. The study concluded with a number of results: The promotion of traditional industry and crafts in Algeria is carried out through a number of mechanisms: the National Award for Traditional Industry, the celebration of the National Day of Traditional Industry, the traditional industry promotion program and the National Fund for the Promotion of Traditional Industry Activities